Age, growth, biological and ecological aspects of Remora osteochir (Echeneidae) in the Mediterranean Sea. (24th June 2015) - Battaglia, P.; Potoschi, A.; Valastro, M.; Andaloro, F.; Romeo, T.
Abstract : This paper provides for the first time data on age and growth of Remora osteochir, also describing its sagittal otolith together with other biological and ecological aspects. Overall, 236 individuals of marlin sucker were collected in the southern-central Mediterranean Sea, from 2008 to 2009. All samples were hosted by the Mediterranean spearfish, Tetrapturus belone, caught by surface longline and harpoon. Analysis of gonads identified a reproductive peak during June and July. The estimated growth parameters according to the von Bertalanffy equation were: L ∞ = 27.37 cm TL, k = 0.248 year −1, t 0 = −1.36 year. The length-weight relationship, computed by using eviscerate weight, highlighted an isometric growth for both sexes, as supported by the other results: similar sizes, growth curves and disc length-total length relationship.